2015
DOI: 10.1186/s12888-015-0412-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk of mental health and nutritional problems for left-behind children of international labor migrants

Abstract: BackgroundOne-in-ten Sri Lankans are employed abroad as International Labor Migrants (ILM), mainly as domestic maids or low-skilled laborers. Little is known about the impact their migration has on the health status of the children they ‘leave behind’. This national study explored associations between the health status of ‘left-behind’ children of ILM’s with those from comparative non-migrant families.MethodsA cross-sectional study design with multi-stage random sampling was used to survey a total of 820 child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
78
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 34 publications
3
78
0
1
Order By: Relevance
“…These papers provide evidence that children left‐behind are more prone to depression, anxiety, and other emotional and mental health problems, in response to the migration of their parents (Graham & Jordan, ; Shi et al., ; Wang et al., ; Zhao et al., ; Zhou et al., ), with children of migrant mothers most affected (Hewage, Bohlin, Wijewardena, & Lindmark, ). Closely related, some studies indicate that children living in migrant families are significantly more likely to have behavioural problems compared with those from nonmigrant households (Vanore et al., ; Wickramage et al., ). It has been shown that problems with personal conduct are more prevalent among male left‐behind children and emotional problems among female children (Graham & Jordan, ; Liu et al., ; Vanore et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…These papers provide evidence that children left‐behind are more prone to depression, anxiety, and other emotional and mental health problems, in response to the migration of their parents (Graham & Jordan, ; Shi et al., ; Wang et al., ; Zhao et al., ; Zhou et al., ), with children of migrant mothers most affected (Hewage, Bohlin, Wijewardena, & Lindmark, ). Closely related, some studies indicate that children living in migrant families are significantly more likely to have behavioural problems compared with those from nonmigrant households (Vanore et al., ; Wickramage et al., ). It has been shown that problems with personal conduct are more prevalent among male left‐behind children and emotional problems among female children (Graham & Jordan, ; Liu et al., ; Vanore et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis found that parental migration was associated with increased risk of mental health problems in Chinese children [8]. LBC were also shown to be prone to loneliness [911], low life satisfaction and depression [12, 13], low self-esteem [14], and behavioral problems [15, 16], in China and globally.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to Wickramage et al. (), in their qualitative approach Siriwardhana et al. () also find that parental absence lead to negative impact on children left behind, while Siriwardhana et al.…”
Section: Literaturementioning
confidence: 55%
“…Improving this limitation, Wickramage et al. () use a nationally representative sample of migrants and find that two in every left‐behind children have mental disorders, male left‐behind children are more vulnerable to psychopathology, emotional and conduct disorders are more prevalent in the male‐caregiver households, and underweight is more prevalent among left behind children of migrants. The authors also find significant associations between child's psychopathological outcomes, child's gender and parent's mental health status.…”
Section: Literaturementioning
confidence: 99%